The Need for Promoting Youth Entrepreneurship in Abakaliki Local Government Area of Ebonyi State, Nigeria - Friday, Onwe; Eze, Eze Ogbonnia; Ekene, Mbam, Philip (American Journal of Social Sciences and Humanities, 2019)
This study looked into the need for promoting youth entrepreneurship in the society, with a particular focus to Abakaliki local government area of Ebonyi state. The term “Entrepreneurship” entails the capacity and willingness to develop, organize and manage a business venture along with any of its risk in order to make a profit at the same time remaining self-sustaining. Most factors which include; low purchasing power have crippled the efforts of good number of youth entrepreneurs in the society, particularly Abakaliki. This study adopted survey design research method for its field work and 94 questionnaires were administered to ninety-four respondents. The data collected are presented using simple percentage table plan for easy understanding. Finally, the result of this study reveals that youth entrepreneurship when promoted is the possible solution to unemployment, poverty, and crime in the society and also the most effective means for the attainment of economic growth. In conclusion, if the youth entrepreneurs are provided with all the support and cooperation they need, over all development will be achieved in the society.